2010
DOI: 10.1038/nbt.1610
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Rescue of the spinal muscular atrophy phenotype in a mouse model by early postnatal delivery of SMN

Abstract: Spinal muscular atrophy (SMA), the most common autosomal recessive neurodegenerative disease affecting children, results in impaired motor neuron function1. Despite knowledge of the pathogenic role of decreased survival motor neuron (SMN) protein levels, efforts to increase SMN have not resulted in a treatment for patients. We recently demonstrated that self-complementary adeno-associated virus 9 (scAAV9) can infect ~60% of motor neurons when injected intravenously into neonatal mice2–4. Here we use scAAV9-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
618
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 660 publications
(651 citation statements)
references
References 31 publications
24
618
1
8
Order By: Relevance
“…Two recent reports have demonstrated that different adeno-associated virus (AAV) vectors expressing SMN cDNA can reach motoneurons and partly rescue newborn mice that would otherwise show a severe SMA phenotype. 109,110 Moreover, neural stem cell therapy may also be an option for treating SMA.…”
Section: The Architecture Of Smn Genes With Regard To Exon 7 Definitionmentioning
confidence: 99%
“…Two recent reports have demonstrated that different adeno-associated virus (AAV) vectors expressing SMN cDNA can reach motoneurons and partly rescue newborn mice that would otherwise show a severe SMA phenotype. 109,110 Moreover, neural stem cell therapy may also be an option for treating SMA.…”
Section: The Architecture Of Smn Genes With Regard To Exon 7 Definitionmentioning
confidence: 99%
“…The issue of a "therapeutic window" is widely discussed in the scientific community since data arising from pre-clinical studies are complex and data from similar human studies are nonexistent. Some pre-clinical studies support the existence of a critical therapeutic window, since increases in SMN levels at post-natal day 1 (P1) rescue the majority of SMA mice, but this rescue is absent if SMN levels are restored later [Foust et al, 2010;Le et al, 2011]. However, other studies did not confirm these findings [Lutz et al, 2011].…”
Section: Therapeutic Window: When Will Treatment Yield the Best Benefit?mentioning
confidence: 99%
“…Several groups are currently evaluating the pre-clinical efficacy of scAAV which have been shown to efficiently infect motor neurons [Foust et al, 2010;Passini et al, 2010;Valori et al, 2010;Dominguez et al, 2011]. Two distinct routes of administration, intravenous (IV) and IT injections, have been tested in pre-clinical models: a better outcome, in terms of survival of the affected mice, has been achieved by IV compared to IT [Foust et al, 2010;Passini et al, 2010;Valori et al, 2010;Dominguez et al, 2011]. However, this therapeutic approach presents some issues: while IT administration could limit the spreading of scAAV infection outside the CNS, potentially reducing the risk of immunization against the virus, it precludes provision of SMN to peripheral tissues.…”
Section: Therapeutic Window: When Will Treatment Yield the Best Benefit?mentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, herpes simplex viruses (HSVs) have been known to enter the CNS by retrograde axonal transport, and HSV has been engineered for remote gene transfer in animal models of disease (15,16). Engineered viruses and protein chimeras have also been used successfully in animal models to transfer therapeutic genes for conditions such as spinal cord injury, spinal muscular atrophy, chronic pain, and amyotrophic lateral sclerosis (17)(18)(19)(20)(21). However, virus-mediated gene therapy has been limited in clinical translation due to issues of immunogenicity, vector safety, and cost of production.…”
mentioning
confidence: 99%